Improving Student Learning Outcomes through Audio Visual Learning Media in Islamic Education Learning at Madrasah Ibtidaiyah Al Aziz Palatiga Baubau City - Hendri; Musfiati (Journal of Indonesian Primary School, 2025)
This study aims to improve Fiqh learning outcomes through the use of audio-visual learning media for students of class III of Al-Aziz Elementary School, Palatiga, Baubau City. This study is a classroom action research on students of class III in even semesters with 15 students and this study is specifically focused on the Fiqh subject, with research procedures, namely planning, action, observation and reflection repeatedly for 2 cycles. The method of data collection is that learning outcome data is taken by giving tests to students after completing the action and learning implementation data is obtained from the results of collaborative observations during the implementation of each cycle using observation instruments for teacher and student activities during teaching and learning activities. With the performance indicator for each student, it is determined that if 80% of each student has achieved a score of ≥70, the student work indicator is an average of 80% have implemented the indicators observed in the student activity observation sheet during the learning process, and the learning process indicator is determined if the learning process activities presented by the teacher reach a good category or 80% have implemented strategy steps using audio-visual learning media. Based on the results of observation, evaluation and reflection in each cycle of action, it can be seen that there is an increase in fiqh learning outcomes after the application of audio-visual learning media in class III students of Madrash Ibtidaiyah Al-Aziz Palatiga, Baubau City. This is indicated by the increasing fiqh learning outcomes in each cycle. In cycle I, 8 students were declared complete or 53.33% with an average score of 66.00 or experienced a classical increase of 33.33% from the pre-cycle, but had not reached the predetermined performance indicators, namely 80% of students scored 70, so this research was continued in cycle II. Furthermore, the learning outcomes after cycle II were 13 students or 86.67% who were declared to have completed the learning with an average score of 78.00 or experienced a classical increase of 33.33% from cycle I. Thus, it can be concluded that the implementation of the use of audio-visual learning media can improve the learning outcomes of fiqh in class III students of Madrasah Ibtidaiyah Al-Aziz Palatiga, Baubau City.